PENGARUH OBSERVASI GEJALA FISIS BERBANTUAN LKS TERHADAP PENCAPAIAN KOMPETENSI SISWA DALAM PELAJARAN FISIKA DI KELAS X SMAN 3 PADANG - Chyntia Arman; Amali Putra; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2016)
Low competence of Physics one of which is caused by the lack of observation of physical phenomena through laboratory activities. This study aims to determine the effect Observation student worksheet Against Assisted Physical Symptoms Student Competence Achievement in Physics Lesson in Class X SMAN 3 Padang. Type of research is a quasi experimental design. The population was all students of class X SMAN 3 Padang enrolled in the Academic Year 2015/2016. Sampling was done by cluster random sampling technique. Samples were class X MIA 5 as an experimental class and class X MIA 6 as the control class. The research data covers the competence of three aspects is attitude, knowledge, and skills. The research instrument is observation sheet for the aspect of attitude, achievement test on knowledge and performance assessment form for the skill aspect. Data were analyzed using two similarity test average on the real level of 0,05. Based on data analysis competence Physics students on aspects of attitudes, knowledge and skills of the experimental class respectively 85,86; 71,28; and 88,69 is higher than the control class that is 82,12; 61,37; and 85,63. The result of the equality of two average by using the t test, obtained t count for each aspect of attitude, knowledge and skills that is 2,43; 4,33; and 6,94. It can be argued that the results Effect of Observation Physical Symptoms Assisted Student Worksheet significant impact Against Student Competence Achievement in Physics Lesson in Class X SMAN 3 Padang on aspects of attitude, knowledge and skills on the real level of 0,05